2021
DOI: 10.1111/aos.14901
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal fluid morphology in chronic central serous chorioretinopathy and its relationship to treatment: a retrospective analysis on PLACE trial data

Abstract: To explore subretinal fluid (SRF) morphology in chronic central serous chorioretinopathy (cCSC) after one session of either high-density subthreshold micropulse laser (HSML) treatment or half-dose photodynamic therapy (PDT). Methods:We retrospectively obtained optical coherence tomography (OCT) scans from a subset of patients from a randomized controlled trial on treatment-na€ ıve eyes with cCSC allocated to either HSML treatment or half-dose PDT. OCT scans were evaluated prior to treatment and 6-8 weeks postt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…However, no predictive role of SRF morphology in treatment response could be extrapolated from that analysis. 20 In our study, our volumetric analysis reported that patients with aCSC had an increased SRF volume at baseline as opposed to cCSC. Feenstra et al described the SRF morphology in patients with cCSC and found that patients presenting the Fuji's sign, characterized by an external limiting membrane displaying a typical concave shape in the context of SRF, were more inclined to have a spontaneous resolution of SRF.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, no predictive role of SRF morphology in treatment response could be extrapolated from that analysis. 20 In our study, our volumetric analysis reported that patients with aCSC had an increased SRF volume at baseline as opposed to cCSC. Feenstra et al described the SRF morphology in patients with cCSC and found that patients presenting the Fuji's sign, characterized by an external limiting membrane displaying a typical concave shape in the context of SRF, were more inclined to have a spontaneous resolution of SRF.…”
Section: Discussionmentioning
confidence: 45%
“…They found that the resolution of the disease was correlated with changes in central macular thickness and subfoveal choroidal thickness, whereas modifications in visual acuity at 12 months were associated with SRF height. 7 SRF morphology in CSC was also previously investigated by Subhi et al, 20 who described the SRF shape modification after halfdose PDT and high-density subthreshold micropulse laser. In this study, half-dose PDT was found to be significantly associated with SRF resolution and volume reduction in comparison with high-density subthreshold micropulse laser.…”
Section: Discussionmentioning
confidence: 88%
“…Initially Ophthalmol Ther for nAMD, but in recent years also for CSC and PCV [15][16][17]. For CSC, this has mainly been based on outcomes of two multicenter randomized controlled trials initiated in the Netherlands, the PLACE and SPECTRA trials, which favored PDT as the preferred firstline treatment [18][19][20][21][22]. Before the shortage, approximately 700 PDT procedures per year were performed in the Netherlands.…”
Section: Unofficial Communication On the Shortage And Deliveries Of V...mentioning
confidence: 99%
“…Patients with CSC typically complain of blurred central vision, metamorphopsia, disturbed color perception, and may experience a hypermetropic change in their refraction. Clinically, macular optical coherence tomography reveals subretinal fluid and a thick choroid [3,4]. Prolonged presence of subretinal fluid should be avoided as irreversible vision loss can occur due to photoreceptor atrophy [5,6].…”
Section: Introductionmentioning
confidence: 99%